PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA: PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL UNTUK MENINGKATKAN PRESTASI - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Learning design can be interpreted from various perspectives, for example as a discipline, as a science, as a system, and as a process. As a discipline, learning design discusses various research and theories about strategies and learning development processes and their implementation. As a science, learning design is the science of creating specifications for the development, implementation, assessment, and management of situations that provide learning service facilities on a macro and micro scale for various subjects at various levels of complexity. As a system, learning design is the development of a learning system and its implementation system including facilities and procedures to improve the quality of learning. Learning design as a process. is a systematic development of learning specifications using learning theory and learning theory to ensure the quality of learning. The development of instructional technology design is rooted in media production. Through a process that takes years this change in media capabilities results in a change in the region. Even though the development of textbooks and other learning aids (print technology) preceded film, the appearance of film is a milestone from the audio-visual movement to the current era of learning technology. In the 1930s, films began to be used for learning activities (audio-visual technology). Learning Technology grew from educational practice and the audio-visual communication movement, originally seen as equipment technology, which is related to the use of equipment, media and means to achieve educational goals or in other words teaching with audio-visual aids. Technological developments certainly have a positive impact on the world of education, because by utilizing learning technology it will be more professional and make teachers and students creative. In the development of instructional technology designs, there are complex interrelationships between technology and theories that drive the design of messages and learning strategies. The design or design of learning technology includes the application of various theories, principles and procedures in planning or designing a program or learning activity that is carried out systemically and systematically.